Feeling younger on active summer days?: on the interplay of behavioral and environmental factors with day-to-day variability in subjective age - Schmidt, Laura; Rupprecht, Fiona; Gabrian, Martina; Jansen, Carl-Philipp; Sieverding, Monika; Wahl, Hans-Werner (Innovation in Aging, 2024)
Subjective age, that is, how old people feel in relation to their chronological age, has mostly been investigated from a macro-longitudinal, lifespan point of view and in relation to major developmental outcomes. Recent evidence also shows considerable intraindividual variations in micro-longitudinal studies as well as relations to everyday psychological correlates such as stress or affect, but findings on the interplay with physical activity or sleep as behavioral factors and environmental factors such as weather conditions are scarce.We examined data from 80 recently retired individuals aged 59-76 years (M = 67.03 years, 59% women) observed across 21 days. Daily diary-based assessments of subjective age, stress, affect, and sleep quality alongside physical activity measurement via Fitbit (steps, moderate-to-vigorous physical activity) and daily hours of sunshine were collected and analyzed using multilevel modeling.Forty-four percent of the overall variance in subjective age was due to intraindividual variation, demonstrating considerable fluctuation. Affect explained the largest share in day-to-day fluctuations of subjective age, followed by stress and steps, whereas sunshine duration explained the largest share of variance in interindividual differences.In our daily diary design, subjective age was most strongly related to self-reported affect as a psychological correlate. We, however, also found clear associations with objective data on daily steps and weather. Hence, our study contributes to contextualizing and understanding variations in subjective age in everyday life.